2019
DOI: 10.7717/peerj.7911
|View full text |Cite
|
Sign up to set email alerts
|

A new goniopholidid crocodyliform,Hulkepholis rorisp. nov. from the Camarillas Formation (early Barremian) in Galve, Spain)

Abstract: BackgroundThe neosuchian crocodyliform genus Hulkepholis constitutes the longirostral lineage of the European Goniopholididae. It comprises two species ranging from the Valanginian of southern England to the lower Albian of the northern Teruel (Spain). A new species of Hulkepholis is described based on a partially complete skull from the lower Barremian Camarillas Formation. We investigate its phylogenetic position and the palatal patterns among members of Goniopholididae and the closely related Thalattosuchia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Halliday et al (2013), however, found the Campanian to Maastrichtian Brachychampsa to be an alligatorine, as did Arribas et al (2019) in a less densely sampled analysis of Crocodyliformes; Bona et al (2018) found it and the newly added Campanian Albertochampsa to be caimanines. In either of these cases, the earliest record of an alligatorid is Brachychampsa sealeyi from early in the Campanian, which began 83.6 ± 0.2 Ma ago (ICS).…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Halliday et al (2013), however, found the Campanian to Maastrichtian Brachychampsa to be an alligatorine, as did Arribas et al (2019) in a less densely sampled analysis of Crocodyliformes; Bona et al (2018) found it and the newly added Campanian Albertochampsa to be caimanines. In either of these cases, the earliest record of an alligatorid is Brachychampsa sealeyi from early in the Campanian, which began 83.6 ± 0.2 Ma ago (ICS).…”
Section: Methodsmentioning
confidence: 90%
“…Given, however, the limited material and the stratigraphic gap between Bottosaurus and the next younger known caimanines, Cossette and Brochu (2018) expressed doubt about the result of their phylogenetic analysis which placed Bottosaurus not only within the caimanine crown-group but next to the extant Paleosuchus. Cossette Halliday et al (2013), however, found the Campanian to Maastrichtian Brachychampsa to be an alligatorine, as did Arribas et al (2019) in a less densely sampled analysis of Crocodyliformes; Bona et al (2018) found it and the newly added Campanian Albertochampsa to be caimanines, a finding expanded by Cossette and Brochu (2020) to Stangerochampsa. In all these cases, the earliest record of an alligatorid is Brachychampsa sealeyi from early in the Campanian, which began 83.6 ± 0.2 Ma ago (ICSC).…”
Section: Node 111: Alligatoridae (Alligatorinae -Caimaninae)mentioning
confidence: 93%
“…Thalattosuchia Fraas 1901 (sensu Young and Andrade 2009) are marine crocodyliforms that lived during the Sinemurian (Lower Jurassic)-Barremian (Lower Cretaceous) interval (Gasparini et al 2000;Jouve et al 2016;Cortes et al 2019). The phylogenetic affinities of the group are uncertain; though most recent analyses have recovered Thalattosuchia as non-eusuchian neosuchians (e.g., Pol et al 2014;Leardi et al 2015;Dal Sasso et al 2017;Ristevski et al 2018;Arribas et al 2019;Fernández Dumont et al 2020;Novas et al 2021). Thalattosuchia comprises two groups, the Teleosauroidea Geoffroy Saint-Hilaire 1831 (sensu Young and Andrade 2009) and the Metriorhynchoidea Fitzinger 1843 (sensu Young and Andrade 2009).…”
Section: Thalattosuchiamentioning
confidence: 99%